The phenomena of self-esteem and audacity in the Andalusian poetesses: Psychological study - Mahmir, Ruqaya; Bouali, Abdulrahman; Jarrar, Salah (Al-Adab Journal, 2023)
Poetry is an emotional state that has different psychological influences behind it. Literature and literary criticism are closely linked to psychology. Any literary work is enveloped in a feeling. What mixes with this feeling are the experience of the creator, the nature of his life, and other factors. Poetry came as a mirror that reflects his spirit and thought, so we find his behavior embedded in the folds. His poetic verses, so psychology comes to unveil the interpretation and analysis, and when comparing the creative woman and the creative man, we find that the female poet is more clear with regard to emotions, and we found her revealing her feelings insinuatingly and frankly, so this research will present two of the psychological phenomena evident in the poetry of Andalusian poets: With self and boldness, in an attempt to stand on it and interpret its causes and goals.